Avaliação neuropsicológica das funções executivas: protocolo breve - Pereira, Victor Hugo Dias (2021)
The advancement of neuropsychology starts to be part of the Brazilian reality, and within the public health services in Brazil there is a reality of increasing demand and evaluation, but there is an instrumental lack for carrying out the evaluations due to the lack of investment in the area. Among the various cognitive domains affected by neurological and psychiatric diseases, Executive Functions (EF) are the most affected, and consequently it generates more losses, since they are responsible for planning and executing tasks aimed at a goal. To try to solve this problem, professionals need low-cost and effective resources in the evaluation and brief evaluations are the ones that stand out in this context. Therefore, this dissertation aims to produce and standardize a brief evaluation protocol for screening for EF for adults. In the first study, a systematic review was carried out that sought to define which instruments are most used in the evaluation of EF. It was found that 58% (f = 19) of the authors considered the instruments they used to assess EF as a brief resource, and 42% (f = 14) mentioned using an evaluative screening resource and it was also identified that the instruments evaluate several cognitive components and that the most used instruments are not specific for EF evaluation. The second study aimed to build and analyze an EF evaluation protocol. The application of the protocol lasted an average of 66 minutes (SD = 7.85) and the tasks that assessed the flexibility factor (rs = 0.445; p = 0.014) and working memory (rs = 0.376; p = 0.041) presented a correlation positive, and it was concluded that a brief protocol is functional for low-cost clinical practice. Considering the findings found in the two studies, it is understood that to fill the lack of assessment instruments in the public service, the built protocol is an alternative that presents itself as effective in clinical application. The limitation of this study is understood as the lack of application of the protocol on a large scale.